2020
DOI: 10.18632/aging.103051
|View full text |Cite
|
Sign up to set email alerts
|

AKT3 deficiency in M2 macrophages impairs cutaneous wound healing by disrupting tissue remodeling

Abstract: AKT signaling and M2 macrophage-guided tissue repair are key factors in cutaneous wound healing. A delay in this process threatens human health worldwide. However, the role of AKT3 in delayed cutaneous wound healing is largely unknown. In this study, histological staining and transcriptomics demonstrated that prolonged tissue remodeling delayed wound healing. This delay was accompanied by defects in AKT3, collagen alpha-1(I) chain (COL1A1), and collagen alpha-1(XI) chain (COL11A1) expression and AKT signaling.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…Col11a1 expression is also highly increased in the neonatal mouse dermis and in mouse dermis that has been reprogrammed to a neonatal stage by epidermal beta catenin activation (Collins et al, 2011). Furthermore, COL11A1 is upregulated upon injection of hyaluronic acid-based dermal fillers (Huth et al, 2020) and downregulation of Col11a1 is associated with delayed wound healing (Gu et al, 2020). These observations might be attributed to our finding that COL11A1 increases the differentiation capacity.…”
Section: Discussionmentioning
confidence: 64%
“…Col11a1 expression is also highly increased in the neonatal mouse dermis and in mouse dermis that has been reprogrammed to a neonatal stage by epidermal beta catenin activation (Collins et al, 2011). Furthermore, COL11A1 is upregulated upon injection of hyaluronic acid-based dermal fillers (Huth et al, 2020) and downregulation of Col11a1 is associated with delayed wound healing (Gu et al, 2020). These observations might be attributed to our finding that COL11A1 increases the differentiation capacity.…”
Section: Discussionmentioning
confidence: 64%
“…In the remodeling phase, the myofibroblasts undergo apoptosis and newly formed granulation tissues are reorganized, and then lead to tissue homeostasis (7)(8)(9)(10)(11). However, interruptions or defects in these delicate phases may lead to a nonhealing wound state (6,12).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, it has been reported that 7-DHC, a cholesterol precursor, regulates type I interferon production via AKT3 activation, where AKT3 directly binds and phosphorylates IRF3 on S385 (64). Additionally, AKT3 (pS473) in macrophages has been shown to promote migration, proliferation, wound healing, and collagen organization (65). Interestingly, a recent study showed that AKT3 phosphorylated RNA processing proteins that regulate the alternative splicing of fibroblast growth factor receptors (FGFR), consistent with an importance of nuclear targeting of AKT3 in EMT maintenance (21).…”
Section: Discussionmentioning
confidence: 99%